Effects of soybean and rice bran oil on hemato-biochemical parameters in mice - Islam, Nafis; Islam, Md Shahidul; Alam, Md Jahangir; Islam, Md Kamrul; Ahmad, Nazim (Research in Agriculture Livestock and Fisheries, 2018)
The study was conducted on “Swiss Albino” mice fed with additional supplementation of soybean oil and rice bran oil to observe the effects on hematological (total erythrocyte count and hemoglobin concentration) and biochemical parameters (total serum cholesterol, triglycerides, high density lipoproteins and uric acid). A total of 30, 6-8 weeks old mice were randomly divided into 3 equal groups (n=10) as A, B and C. Group A was considered as control (fed only commercial ration), group B was supplemented with rice bran oil and group C treated with soybean oil respectively in addition to commercial ration for 60 days. At the end of feeding trial the mice were sacrificed for analysis of hematobiochemical parameters. The total erythrocyte count and hemoglobin concentration were increased significantly (P<0.05) in group B and C compared to control group A and the highest values was recorded in soybean oil group C. The total serum cholesterol, triglycerides, HDL and uric acid were increased significantly (P<0.05) in both rice bran oil and soybean oil group compared to control group. It is concluded that some hemato-biochemical parameters of blood in the mice are affected by rice bran and soybean oil enriched diet. Though, oils and fats are detrimental to health but to evaluate the effects of rice bran and soybean oil, further studies with more animals and some other parameters like liver function, kidney function may be conducted. Res. Agric., Livest. Fish.5(3): 365-372, December 2018